Scientific approaches to the formation of the classification of regime-forming objects and restrictions (on the example of territories of water objects) - Dorosh, Y.; Barvinskyi, A.; Kharytonenko, R.; Bratinova М. (Land Management, Cadastre and Land Monitoring, 2021)
Scientific approaches to the role of regime-forming objects in the formation of restrictions on land use, which have been studied by scholars of economic and legal profiles, are considered. The approaches to the formation of the classifier of regime-forming objects by certain relevant groups in relation to the zones with the limited regime of land use and the territories that are formed around them are analyzed. The classification of territorial restrictions by groups and their territorial restrictions on land use is given. It is established that in the current legislative and regulatory framework there is no classification of regime-forming objects that form restrictions on land use. The list of restrictions on land use, land plots, as well as the list of territorial zones do not contain a complete list of possible regime-forming objects in land use, which needs to be clarified and supplemented. The list of restrictions on the use of land (land plots) and territorial zones is analyzed on the example of the territories of water bodies in accordance with current legislation. It is established that the existing information on restrictions on land use (land plots) on the example of water bodies, which is reflected on the Public Cadastral Map of Ukraine, is characterized by conditional (visual) reflection, which creates conflicts and abuses in determining such restrictions. Keywords: classification, regime-forming object, restrictions on land use, territories of water bodies.